1998
DOI: 10.4141/a98-049
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for milk yield and litter size in Boutsico dairy sheep

Abstract: Kominakis, A., Rogdakis, E. and Koutsotolis, K. 1998. Genetic parameters for milk yield and litter size in Boutsico dairy sheep. Can. J. Anim. Sci. 78: 525-532. Lactation and litter size records (n = 2553) of Boutsico dairy sheep were used to estimate direct additive, maternal genetic, maternal and animal's permanent environmental variance components for milk yield and litter size by restricted maximum likelihood under a repeated records animal model. Raw milk yield data were transformed by log and Box-Cox (BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
11
0
3
Order By: Relevance
“…In Spanish Merino sheep, estimates of r m between weight at 30, 60, and 90 d and litter size ranged from −.05 to .03 (Analla and Serradilla, 1998). Kominakis et al (1998) reported an estimate of the additive direct correlation between litter size and actual milk yield of .13 in Boutsico dairy sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Spanish Merino sheep, estimates of r m between weight at 30, 60, and 90 d and litter size ranged from −.05 to .03 (Analla and Serradilla, 1998). Kominakis et al (1998) reported an estimate of the additive direct correlation between litter size and actual milk yield of .13 in Boutsico dairy sheep.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Al-Shorepy and Notter (1996) reported h 2 estimates for litter size in fall and in combined fall and spring lambings of .10 and .05, respectively. Altarriba et al (1998) obtained an estimate of h 2 for litter size of .077 ± .017 in Rasa Aragonesa sheep using a threshold model, and Kominakis et al (1998) reported an estimate of h 2 for litter size of .06 ± .03 for Boutsico dairy sheep in Greece.…”
Section: Discussionmentioning
confidence: 99%
“…Two typical indigenous breeds, Chios and Boutsiko, along with a synthetic breed were used in this study. The Chios breed is characterized by high milk yield and litter size, whereas the lessproductive Boutsiko breed is known for its adaptability under harsh environmental conditions and its reduced susceptibility to mastitis (Hatziminaoglou et al, 1990;Simos et al, 1996;Kominakis et al, 1998;Ploumi et al, 1998). The synthetic breed (50% Boutsiko, 25% Arta, and 25% Chios) has been recently formed in an attempt to upgrade the Boutsiko breed by combining the high productivity of the Chios and Arta breeds with the robustness of the Boutsiko breed.…”
Section: Introductionmentioning
confidence: 99%
“…Boutsko, Sfakia and Lesvos). These studies showed that improvement of important traits was possible through selection (Kominakis et al, 1998;Ligda et al, 2000;Mavrogenis and Papachristoforou, 2000;Kominakis et al, 2002;Ligda et al, 2003;Nikolaou et al, 2004). Milk yield and composition were found to be antagonistically correlated indicating that selection for one trait would adversely affect the other (Volanis et al, 2002).…”
Section: Dairy-related Traitsmentioning
confidence: 99%